Effect of quick-dip with increasing doses of IBA on rooting of five grapevine rootstocks grafted with 'Cabernet Sauvignon' - Gordillo, María Gabriela (2022)
The establishment of a vineyard depends on clonal propagation of grapevine woody cuttings. The successful plant propagation relies on adventitious root formation, but it is affected by the scion-rootstock interaction. Synthetic auxins are used in the nursery to improve rooting of woody cuttings. We tested the effect of a quick dip (30 seconds) of increasing doses of indole-3-butyric acid (IBA) solutions (0, 500, 750, 1000, 1250, 1500 ppm) on rooting of grafted woody cuttings. We tested 5 rootstocks grafted with V. vinifera 'Cabernet Sauvignon': SO4 (V. berlandieri x V. riparia), 110 Richter and 1103 Paulsen (V. berlandieri x V. rupestris), 101-14 Mgt (V. riparia x V. rupestris) and Cereza (V. vinifera L.). After 21 days in the callus chamber, we examined the quality of the root system by means of different rooting parameters (callusing and rooting percentage and number, length and biomass of roots per cutting). Among all the rooting parameters evaluated, Cereza presented the highest values in relation to the rest of the rootstocks, followed by 101-14 Mgt, SO4, 110R and 1103P. The quality of the root system was improved in terms of number of roots, length and the total biomass on four rootstocks: Cereza, 110R, 101-14 Mgt and SO4, but not in 1103P whose rooting was unaffected by treatments. The optimal dose of IBA through quick-dip at improving rooting was rootstock-dependent, being 750 ppm for 110R, 101-14 Mgt and SO4; and 1000 ppm for Cereza. These results will contribute in reducing costs during clonal propagation in the nursery, which is associated with the use of costly synthetic hormones and a lower production of bare-root vines.